Role of urinary biomarkers in the prognostic assessment of lupus nephritis - HUANG Biyao, LI Wengen (Xin yixue)
Lupus nephritis （LN） is a major cause of mortality and morbidity in patients with systemic lupus erythematosus （SLE）. Previous studies have shown that the pathological types of LN can transform， and these types serve as critical bases for formulating individualized treatment plans and predicting disease progression in SLE patients， thereby improving survival rates and quality of life. Renal pathology remains the “gold standard” for diagnosing LN and can be used to monitor disease progression and assess the therapeutic efficacy. However， renal pathology requires invasive renal biopsy， creating an urgent need for non-invasive biomarkers for LN diagnosis， disease activity monitoring， and treatment evaluation. Current research on biomarkers for disease monitoring primarily focuses on blood-derived biomarkers. In contrast， urinary biomarkers offer advantages such as ease of collection， non-invasiveness， and the ability for continuous short-term monitoring. Compared to renal biopsy and blood biomarkers， urinary biomarkers demonstrate significant advantages in diagnosing and monitoring LN. Emerging studies on urinary biomarkers for LN prognosis are on the rise. This review summarizes recent advances in the role of urinary biomarkers for LN prognosis assessment， thereby providing a reference for the clinical diagnosis and treatment of LN.